Digital responsibility insights from a cross-cultural design thinking workshop for creativity - Lee, Hyun-Kyung; Park, Joo Eun (Creativity Studies, 2022)
To be digitally responsible, one should be aware of the current issues in the digital world; therefore, raising awareness on digital responsibility and data privacy is important in the public and private sectors. This study aimed to raise awareness on digital responsibility and help students understand the importance of utilizing the design thinking process for generating creative ideas. The authors facilitated a design thinking workshop where 62 students from different cultural backgrounds (Korean and Swiss) and majors collaboratively explored data privacy issues and presented their novel, creative solutions. The data gathered from observations and interviews were analyzed using qualitative content analysis. These students of the digital age developed remarkable ones, such as keeping data safe from social networking services and protecting voice data from being recorded by a third party. The cross-cultural, interdisciplinary team rapidly implemented their creative and globally applicable solutions with visually feasible, diagrammed prototypes, which is an effective tool of the design thinking process. The article demonstrates how design thinking techniques could be applied in university classes and could inspire teachers to use the five stages of design thinking in their teaching.